A review of rheological properties of high quality cassava flour (HQCF) composites. - Okoko, J. U.; Alonge, A. F.; Ngoddy, P. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Food products development by means of composite flour technology is experiencing a remarkable upsurge globally with the ticking of the clock; thereby inviting a great deal of researchers’ consideration, particularly in bakery foodstuffs and pastries making. The world population is increasing and is projected to be well over eight billion people in the year 2030, with attendant imports of an increased consumption, hence higher demands for processed foods such as bread. In view of the climb in consumption of bread, a higher demand for wheat should be in anticipation. Thus, shrinkage in the global supply of wheat as a resource in the immediate future should be anticipated. This development gives emphasis to the necessity for alternative sources of flour and starch. The attention of this review is directed at the studies of rheological characteristics of composite flour vis-à-vis its consumptions via food products such as bread, biscuits, and pasta. Emphasis is on blends which have high quality cassava flour (HQCF) or just cassava flour as one of the compositing flours with its influence on the sensory and nutritional qualities in addition to its universal approval. In this work, a report has also been given of a study on wheat flour blended in varying proportions with other flours such as those from rhizomes, legumes, fruits and cereals (other than wheat) to create diverse food products. Cassava flour in bread making has been found to be a suitable substitute for encouraging the utilization of a local produce besides reduction of wheat flour imports and upholding the production of high quality cassava flour (HQCF). The development of gluten-free products and fortification of foods have also turned out to be a possibility. Several researchers have developed a range of breads using cassava flour whose properties are akin to those of wheat flour breads. It is promising that the capability of composite flour in bakery and pastry products to retain similar properties to products made from pure wheat flour has been reported. It has also been testified that the use of composite flours has acceptable impacts on the finishing products from the standpoint of functional and physicochemical characteristics as well as healthiness of the end users. Generally, composite flour technology is being regarded as a noble new method for harnessing the benefits in flours that may not unfold unless in composites, which of course, as a matter of fact, will be contingent upon the proportions of blending.